Day 2 Tue, October 16, 2018 2018
DOI: 10.2118/191720-18rptc-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experience and Optimization of Essential Multistage Fracturing Technology with Coiled Tubing at the Well for the Vinogradova Oilfield

Abstract: In the article presented 2 years of experience gained during multi-stage hydraulic fracturing (MSF) on 17 wells, by means of coiled tubing (CT) without lifting it to the surface, performed in years 2017 – 2018 on Vinogradova oilfield, KhMAO, Russia. In 2017 it was successfully implemented innovative technology, where fracturing operations are combined with coiled tubing (CT) operations and are run together with CT inside the well. Current method is based on operating reusable fracturing ports, where opening an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Qin et al [14] adopted a new OH horizontal well sliding sleeve multistage fracturing tool according to the geological conditions, fracture treatment, well trajectory, and diameter changes of the open-hole horizontal wells with long horizontal sections in the Daniudi gas field and Honghe oilfield, which was then satisfactorily applied in more than 20 horizontal wells in the Ordos Basin. Parshin et al [15] demonstrated the successful application of the coiled tubing multistage hydraulic fracturing technology in the AS3 reservoir of Vinogradova Oilfield, which significantly improved the production performance of wells.…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al [14] adopted a new OH horizontal well sliding sleeve multistage fracturing tool according to the geological conditions, fracture treatment, well trajectory, and diameter changes of the open-hole horizontal wells with long horizontal sections in the Daniudi gas field and Honghe oilfield, which was then satisfactorily applied in more than 20 horizontal wells in the Ordos Basin. Parshin et al [15] demonstrated the successful application of the coiled tubing multistage hydraulic fracturing technology in the AS3 reservoir of Vinogradova Oilfield, which significantly improved the production performance of wells.…”
Section: Introductionmentioning
confidence: 99%